Developing cross-cultural competence a guide for working with children and their families - Lynch, Eleanor W.; Hanson, Marci J. (P. H. Brooks Pub., 1998)
The updated second edition of this popular resource offers practical advice for working with children and families of diverse heritage. With insight from their own racial, cultural, and linguistic backgrounds, the chapter authors contribute wisdom about the influence of different cultures on people's beliefs, values, and behaviors. Their knowledge helps professionals learn how to embrace diversity in intervention services and foster respectful and effective interactions with people of many cultures. Widely used in preservice and in-service settings, Developing Cross-Cultural Competence is invaluable as a textbook in graduate and undergraduate courses in general and special education, social work, child development, psychology, family studies, and public health and ideal as a guide for human services professionals, home visitors, paraprofessionals, and program administrators who work with children with disabilities.